O lugar do nutricionista nos núcleos de apoio à saúde de Fortaleza: desenhos iniciais - Rodrigues, Diana Cris Macedo (2012)
The food and nutritional problems in the contemporary world, the epidemiological and nutritional profile in Brazil, the assumption of the Food and Nutritional Security and the Human Right to Adequate Food as a priority of state and the need of strengthening actions of nutritional care in the Strategy of Family Health (FHS) as an essential part of integral health care in the Networks of Health Care, are the main reasons that justify the inclusion of the strategic area of food and nutrition in the Center for Family Health Support (CFHS) proposal. The insertion of the nutritionist in this proposal intends to contribute to the qualification of the actions in this area of care, by conducting an interdisciplinary work, sharing knowledge and practices with teams from Family Health. The aim of this work was to understand perceptions of nutritionists who work in CFHS in Fortaleza concerning its inclusion in the FHS. It is a research oriented by a qualitative approach, grounded on epistemological foundations of phenomenology and hermeneutics. In order to access the subjective production of nutritionists it was used the in-depth interview, choosing to the possible extent, the nondirective procedure. The categorization of the empirical material led us to three central axes: 1) Insertion at FHS, 2) Perceptions about the context, 3) The Nutritionist at Family Health Strategy. Each axis was split into different dimensions. The findings revealed that the CFHS appears as another job opportunity arose, in which professionals have structured their work process taking a largely individualistic and technical practice with little consideration on their performance. The Unique System of Health and FHS present themselves as health services restricted to poor people, revealing how little the discussion on health policy is widespread among the professionals who operate the services. In this context, carrying out activities in a community attempting to prevent diseases is considered the main task of the CFHS. The findings show that the CFHS has organized its doing mostly from direct assistance to the user, carrying out a work disjointed from the Family Health team. Interfaces perceived between the CFHS and FHS relate to disease prevention, being almost absent the mention to the pedagogical support to the Family Health teams. Industrialization, standardization, dispossession of eating, the traps of the food industry in advertising and inconsistencies between lifestyles sold by the media and the living conditions of most users and the epidemic of obesity are major issues present in food and nutrition territories assisted by professionals. In this scenario, most professionals conceive the place of the nutritionist in the prevention and treatment of diseases and disorders related to food, and his actions are dedicated at changing eating habits through a nutrition education focused on food exchanges aiming to rationalize the resources available in favor of consumption healthier foods. Accordingly, the findings indicate the professionals posture against the ideology of the project of Brazilian Health Reform and the principles of Food and Nutritional Safety policies, pointing out the distances between their actions and the current health needs of the population assisted.